2014
DOI: 10.1177/0020764014540149
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal sex differences of externalising and internalising depression symptom trajectories: Implications for assessment of depression in men from an online study

Abstract: Findings contribute to the validity of the MDRS-22 as a measure of externalising depression symptoms. Results suggest that while both males and females experience externalising depression symptoms, these symptoms may be particularly elevated for men following experiences of negative life events. Findings suggest that externalising symptoms may be a special feature of depression for men. Given the problematic nature of such externalising symptoms (e.g. excessive substance use, aggression, risk-taking), their cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 13 publications
3
35
0
3
Order By: Relevance
“…DSM-IV andDSM 5 (American Psychiatric Association, 2000, 2013) were used to identify standard criteria for depression. Alternative criteria were identified on the basis of previous evidence in the research literature (Martin et al, 2013;Rice et al, 2015). See Table 1 for a list of alternative criteria included in the study.…”
Section: Sample and Instrumentmentioning
confidence: 99%
“…DSM-IV andDSM 5 (American Psychiatric Association, 2000, 2013) were used to identify standard criteria for depression. Alternative criteria were identified on the basis of previous evidence in the research literature (Martin et al, 2013;Rice et al, 2015). See Table 1 for a list of alternative criteria included in the study.…”
Section: Sample and Instrumentmentioning
confidence: 99%
“…Additionally, some have suggested that sex differences in the epidemiology of depression may be partly related to the absence of “male-typical,” externalizing symptoms from standard diagnostic criteria (Martin, Neighbors, & Griffith, 2013; Rice et al, in press ). …”
mentioning
confidence: 99%
“…However, it has been challenging to disentangle the various biological, psychological, and cultural contributors to these sex/gender gaps in humans (Mogil, 2012), despite recent findings implicating different cellular mechanisms of pain sensitivity in male and female mice of certain strains (Sorge et al, 2015). Neuroimaging and electroencephalography have yet to reveal a clear neural basis for sex/ gender difference in human pain processing, nor do other physiological or hormonal measures demonstrate an obvious mechanism for differences in pain threshold and tolerance (Racine et al, 2012b;Bartley and Fillingim, 2013).…”
Section: Gender Dimensions Of Male-female Differences In the Human Brmentioning
confidence: 99%
“…Among adults, gender differences in pain thresholds and tolerance are often reduced or eliminated in studies that control for individual differences in anxiety, gender role endorsement, selfefficacy, and coping style (Jackson et al, 2002;Fillingim et al, 2009;Mogil, 2012). Other social variables, including cultural origin and the gender of the experimenter, also modify sex/gender differences in pain perception (Racine et al, 2012b). When it comes to clinical practice, even a leading researcher on animal sex difference concedes that analgesic treatments must always be titrated on an individual basis, where biological sex is but one of many sources of interindividual variability (Mogil, 2012).…”
Section: Gender Dimensions Of Male-female Differences In the Human Brmentioning
confidence: 99%